Clinical Data Mining of Phenotypic Network in Angina Pectoris of Coronary Heart Disease. (12th June 2012) - Chen, Jianxin; Lu, Peng; Zuo, Xiaohan; Shi, Qi; Zhao, Huihui; Luo, Liangtao; Yi, Jianqiang; Zheng, Chenglong; Yang, Yi; Wang, Wei
Abstract : Coronary heart disease (CHD) is the leading causes of morbidity and mortality in China. The diagnosis of CHD in Traditional Chinese Medicine (TCM) was mainly based on experience in the past. In this paper, we proposed four MI-based association algorithms to analyze phenotype networks of CHD, and established scale of syndromes to automatically generate the diagnosis of patients based on their phenotypes. We also compared the change of core syndromes that CHD were combined with other diseases, and presented the different phenotype spectra.